ماهية الدلالة المعجمية ومراحلها - Eva Dewi (UIN Fatmawati Sukarno Bengkulu, 2018)
Dictionaries, a book that includes the largest number of vocabulary combined with explaining and interpreting their meaning, to be material arranged a special arrangement: either the letters of the alphabet, or on the subject. It is called a dictionary because the nouns remove the confusion and clarify the vagueness. The complete of dictionary, which includes every word in accompanied by explaining its mean and its derivation and the method of its pronunciation and evidence showing its language positions used.Lexicology is the part of linguistics that interest with the study of words, its nature and its mean, the elements of words, the relations between words (semantic relationships), the sets of words and the study of each lexicon of a language. The linguists divided the stages of language collection into several stages, each stage different from one another, everything will be discussed in this article